Integration of Digital Technology in the Empowerment of Songkok Recca Micro, Small, and Medium Enterprises (MSMEs) - Andi Amitya Resty Dwiyanti; Syaripa Aeni MR; Misnawati Misnawati (Mahesa Research Center, 2024)
This study aims to evaluate the effectiveness of government policies in supporting the empowerment ofSongkok ReccaMicro, Small,and Medium Enterprises (MSMEs) in Bone Regency, with a particular focus onintegratingdigital technology. A qualitative research approach with a case study method was used to explore the experiences of MSME players in adopting digital technologyandthe role of government support in improving competitiveness, innovation, and the quality of human resources (HR). Data was obtained through in-depth interviews with MSME players, representatives from the Bone Regency Cooperative and MSME Office, and direct observation of the operational process at theSongkok ReccaMSME. The results show that government policies in terms of digital marketing have had a positive impact on market expansion and increased MSME revenues. However, significant challenges remain related to lowproduction technology adoption, high raw material costs, and difficulties adapting to digital platforms, especially among older MSME players. The government is advised to provide more holistic support, includingintroducingappropriate production technologies anddevelopinglocal raw material supply chains. With a more comprehensive approach, the empowerment ofSongkok ReccaMSMEs can contribute more significantly to local and national economic growth.